Preclinical and Clinical Evaluation of Magnetic-Activated Cell Separation Technology for CTC Isolation in Breast Cancer - Lozar, Taja; Jesenko, Tanja; Kloboves Prevodnik, Veronika; Cemazar, Maja; Hosta, Violeta; Jericevic, Anja; Nolde, Natasa; Grasic Kuhar, Cvetka (Frontiers in Oncology, 2020)
Circulating tumor cell count is an independent prognostic factor in early breast cancer. CTCs can be found in the blood of 20% of patients prior to neoadjuvant therapy. We aimed to assess the suitability of magnetic-activated cell separation (MACS) technology for isolation and cytological characterization of CTCs. In the preclinical part of the study, cell lines were spiked into buffy coat samples derived from healthy donors, and isolated using MACS. Breast cancer cells with preserved cell morphology were successfully isolated. In the clinical part, blood for CTC isolation was drawn from 44 patients with early and locally advanced breast cancer prior to neoadjuvant chemotherapy. Standard Giemsa, Papanicoulau and pancytokeratin staining was applied. 2.3% of samples contained cells that meet both the morphological and immunocytochemical criteria for CTC. In 32.6% of samples, partially degenerated pancytokeratin negative cells with morphological features of tumor cells were observed. In 65.1% of samples, CTCs were not found. In conclusion, our results demonstrate that morphologically intact tumor cells can be isolated using MACS technology. However, morphologically intact tumor cells were not detected in the clinical part of the study. At present, MACS technology does not appear suitable for use in a clinical cytopathology laboratory.